2015
DOI: 10.1016/j.molcel.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

PKCs Sweeten Cell Metabolism by Phosphorylation of Glut1

Abstract: In this issue, Lee et al. (2015) show that PKC directly phosphorylates the glucose transporter Glut1, in order to promote glucose uptake in response to growth factor signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Moreover, GLUT1 silencing suppressed PKC-iota-mediated 18 F-FDG accumulation and subsequent glycolysis in NSCLC cells. Taken together, we confirmed that PKC-iota regulated glycolysis via c-Myc/GLUT1 signaling; the regulatory effect of PKC-iota on GLUT1 occurred at the transcriptional level; the most likely reason for the decrease in active, membrane-located GLUT1 induced by PKC-iota knockdown, which was also observed in our research, is the overall decrease in GLUT1 induced by c-Myc downregulation, which might differ from direct phosphorylation and activation of GLUT1 by other PKCs at the post-translational level 14…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, GLUT1 silencing suppressed PKC-iota-mediated 18 F-FDG accumulation and subsequent glycolysis in NSCLC cells. Taken together, we confirmed that PKC-iota regulated glycolysis via c-Myc/GLUT1 signaling; the regulatory effect of PKC-iota on GLUT1 occurred at the transcriptional level; the most likely reason for the decrease in active, membrane-located GLUT1 induced by PKC-iota knockdown, which was also observed in our research, is the overall decrease in GLUT1 induced by c-Myc downregulation, which might differ from direct phosphorylation and activation of GLUT1 by other PKCs at the post-translational level 14…”
Section: Discussionsupporting
confidence: 75%
“…PKC-iota is the first PKC reported as an oncogenic enzyme in NSCLC,10 and contributes to tumor progression via immune suppression, cell cycle deregulation, and pericellular degradation of the extracellular matrix 1113. Although other PKCs were reported to directly phosphorylate glucose transporter 1 (GLUT1), which is the key rate-limiting carrier in charge of glucose transportation, thereby promoting its activation and the transport of glucose across plasma membranes,14 the regulatory effect of PKC-iota on GLUT1 is not yet well established. Whether PKC-iota is involved in glucose metabolism in tumors remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells consume nutrients and in particular, glucose to sustain their proliferation, restricting glucose availability to TILs (67). Glucose deprivation impedes CD8 + TIL effector function by limiting aerobic glycolysis, decreasing mTOR activity and IFN-γ production.…”
Section: Metabolic Checkpointsmentioning
confidence: 99%
“…GLUT1 was also suggested to be the receptor for human T‐lymphotropic virus (HTLV) and play an essential role in CD4 T cell activation . The transport activity of GLUT1 is subjected to regulation by PKC and TXNIP . Several dozens of SLC2A1 mutations have been identified in patients with the autosomal dominant genetic disease known as GLUT1 deficiency syndrome …”
Section: Physiological Functions Of Glucose Transportersmentioning
confidence: 99%